Motivation and reconciliation in Catherine Lu's conception of global justice. Issue 1 (1st January 2018) - Digeser, Paige E.
ABSTRACT: In Justice and Reconciliation in World Politics (2017), Catherine Lu argues that those of us who have been thinking about problems of justice in the aftermath of cataclysmic international events have been aiming too narrowly and too low.  We have been aiming too narrowly in the sense that we have focused too much attention on states and individuals as responsible parties and not enough on international structures.  In other words, there are multiple sites of justice and all the action is not to be found at the level of interpersonal or interstate interactions. Much of Lu's discussion of structure is drawn directly from Iris Marion Young's work (or, at least, one version of Young). In addition, we have aimed too low by not devoting attention to the widespread forms of alienation that are the result of events and persistent unjust international structures (the case that she returns to throughout the text is that of colonialism). She calls for a more historical and sociological turn in the literature on transitional justice. This essay raises a few questions regarding the ideas of culpability and motivation in Lu's account of structural justice.  In particular, if focuses on Lu's use of Young and then concludes with a brief consideration of her notion of alienation.